Report of the Committee on The Financial System - Planning Commission (Planning Commission, 1991)
The Committee's approach to the issue of financial sector reform Is to ensure that the financial services Industry operates on the basis of operational flexibility and functional autonomy with a view to enhancing efficiency, productivity and profitability. A vibrant and competitive financial system Is also necessary to sustain the ongoing reform in the structural aspects of the real economy. We believe that ensuring the Integrity and autonomy of operations of banks and DFIs Is by far the more relevant issue at present than the question of their ownership.
Report of the Committee on The Financial System
Planning Commission